European Sustainability Transitions in the Perspective of Democratic Experimentalism - Quintão, F.; Esteves, A. (28th International Conference of Europeanists, 2022)
The imbrication of environmental and democratic crises has deep roots, and the responses to these crises come from a wide range of perspectives and point towards diverse directions. In the European context, the idea of sustainability transitions has constituted a field of investigation both academically and practically, with institutions like the Sustainability Transitions Research Network (STRN) and the Transition Movement. This presentation aims to critically analyze this field, trying to outline the narratives of change proposed by Its actors and putting them in perspective with the discussion about democratic experimentalism. The data comes from a literature review, both of the conceptual frames around the ideas of sustainability transitions and the practical experience of collective action linked to the Transition Movement. Fieldwork will be consisting of participative observation and interviews with actors linked to the Transition Portugal collective, which brings together community-led initiatives around the country.